2012
DOI: 10.1016/j.comppsych.2011.08.003
|View full text |Cite
|
Sign up to set email alerts
|

A survey of psychosis risk symptoms in Kenya

Abstract: Defining the pre-psychotic state in an effort to prevent illness progression, and the development of disorders such as schizophrenia, is a rapidly growing area of psychiatry. The presentation of psychotic symptoms can be influenced by culture; however there has not been any previous assessment of psychosis-risk symptoms in the continent of Africa. Our study aimed to measure the prevalence of psychosis-risk in a community sample in Nairobi, Kenya, and to evaluate the effects of key demographic variables. A cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 38 publications
5
29
0
Order By: Relevance
“…Written and signed consent was obtained from the study participants and the study was approved by the institutional review board of Washington University Medical School, the Kenyan Medical Research Institute, and the Ministry of Education, Science, and Technology, Kenya. A total of 2758 individuals between the ages of 14 and 29 were recruited for our prior survey using mPRIME, as detailed in Mamah et al [25]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Written and signed consent was obtained from the study participants and the study was approved by the institutional review board of Washington University Medical School, the Kenyan Medical Research Institute, and the Ministry of Education, Science, and Technology, Kenya. A total of 2758 individuals between the ages of 14 and 29 were recruited for our prior survey using mPRIME, as detailed in Mamah et al [25]. …”
Section: Methodsmentioning
confidence: 99%
“…Our group previously examined psychosis risk in young Kenyan populations using a slightly modified version of the PRIME screen to account for cultural differences in screen item interpretation (mPRIME), and found that 45.5% of participants aged 14 to 29 reported having had a psychosis risk symptom (i.e., a score of ‘6’) on the screen [25]. The main goal for the current study was to evaluate the validity of the mPRIME as a screening tool for general youth populations, using the SIPS as the reference standard.…”
Section: Introductionmentioning
confidence: 99%
“…72 A community study of youth aged 14 to 29 years from Kenya reported that 45% of the sample endorsed at least 1 psychotic risk symptom. 73 These experiences do not necessarily predict the onset of a psychotic disorder; rather, they are apt to be indicators of risk for a variety of mental disorders (including depression, bipolar disorder, and sometimes schizophrenia). Even when psychotic symptoms do represent a prodrome for psychotic disorders (usually schizophrenia spectrum disorders), approximately 18% to 36% of people defined as high risk go on to transition to a mental disorder, with the risk of transition increasing over time.…”
Section: Research Priority Setting For Global Mental Healthmentioning
confidence: 99%
“…Identifying who is at risk to transition to a psychotic disorder, and intervening early, remains a critical area for investigation. Efforts to harmonize data across research sites in HICs enrich these research activities, but questions remain about the validity of commonly used measures to assess those who may be at high risk for psychosis in low-income country settings 73 (see Table 1). …”
Section: Research Priority Setting For Global Mental Healthmentioning
confidence: 99%
“…Differences in health care systems and patterns of referral for specialized care affect the ways in which high risk individuals can be identified for research purposes and the implementation of intervention research. Base rates of self-reported psychosis prodrome symptoms appear to differ among countries [ 21 , 22 ], thus impacting estimates of prevalence and conversion rates. Translation and validation of the measures used to detect the psychosis risk state facilitates data sharing and integration across countries and cultures.…”
Section: Reviewmentioning
confidence: 99%